Management Rights - Norcott, W.F.; Bennett, R.M.; Robert, C.-Marc (Relations industrielles / Industrial Relations, 1958)
SummarySome months ago (December 5th, 1957), the Employee Relations Section of THE MONTREAL BOARD OF TRADE sponsored a panel discussion on the very important and much debated question of MANAGEMENT RIGHTS. Here follow the VERBATIM contributions of three of the four participating panelists: Mr. W.F. Norcott (Personnel Manager, Gillette of Canada Limited), Mr. R.M. Bennett (Secretary-Treasurer, Montreal Typographical Union, No. 176), and Mr. C.-Marc Robert (Personnel Manager, Canadian General Electric Co., Ltd).